2012
DOI: 10.1371/journal.pone.0045829
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Fusion Is Essential for Steroid Biosynthesis

Abstract: Although the contribution of mitochondrial dynamics (a balance in fusion/fission events and changes in mitochondria subcellular distribution) to key biological process has been reported, the contribution of changes in mitochondrial fusion to achieve efficient steroid production has never been explored. The mitochondria are central during steroid synthesis and different enzymes are localized between the mitochondria and the endoplasmic reticulum to produce the final steroid hormone, thus suggesting that mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
144
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(155 citation statements)
references
References 54 publications
9
144
0
2
Order By: Relevance
“…In addition, we could determine that some markers of adipose tissue beiging were upregulated in adipose tissues from LS mice, notably in s.c. fat pads, suggesting that this adipose tissue has enhanced oxidative activity, which could contribute to enhanced energy expenditure. Interestingly, several studies have shown that SHP2 could regulate mitochondria activity, although the signaling pathways that link SHP2, and its LS-associated mutants, to the regulation of mitochondria function and energy homeostasis remain to be documented (37)(38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we could determine that some markers of adipose tissue beiging were upregulated in adipose tissues from LS mice, notably in s.c. fat pads, suggesting that this adipose tissue has enhanced oxidative activity, which could contribute to enhanced energy expenditure. Interestingly, several studies have shown that SHP2 could regulate mitochondria activity, although the signaling pathways that link SHP2, and its LS-associated mutants, to the regulation of mitochondria function and energy homeostasis remain to be documented (37)(38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SHP2 is needed for the correct association of ERK with mitochondria, as an indirect way of controlling StAR phosphorylation by ERK activity (Duarte et al, 2012).…”
Section: Phosphatases In Star Functionmentioning
confidence: 99%
“…Mfn2 is promptly up-regulated after the steroidogenic stimuli, thus suggesting that mitochondrial dynamics might be central for steroidogenesis. Furthermore, blocking mitochondrial fusion by knocking down Mfn2 expression has a negative impact on steroid synthesis (Duarte et al, 2012). The changes observed in mitochondrial fusion might also be central for the formation of the mitochondrial multiprotein complex that delivers cholesterol to the P450scc system, as hormone-stimulated mitochondrial rearrangement is required for the re-localization of the ERK1/2 protein to mitochondria.…”
Section: Mitochondrial Dynamics In Steroid Synthesismentioning
confidence: 99%
“…Of particular interest, mitotane exposure also triggered morphologic fragmentation of the mt network, which could be related to disequilibrium between mt fission and fusion . It is well established that the integrity of mt outer and inner membranes is required for respiratory chain activity (Liesa et al 2009) and presumably steroidogenesis (Duarte et al 2012). It is not known, however, whether mt fragmentation has a direct relationship with or a causal role in genotoxic stress and apoptosis.…”
Section: Figurementioning
confidence: 99%